An Approximation of Semigroups Method for Stochastic Parabolic Equations - Allaberen Ashyralyev; Mehmet Emin San (Abstract and Applied Analysis)
A single-step difference scheme for the numerical solution of the nonlocal-boundary value problem for stochastic parabolic equations is presented. The convergence estimate for the solution of the difference scheme is established. In application, the convergence estimates for the solution of the difference scheme are obtained for two nonlocal-boundary value problems. The theoretical statements for the solution of this difference scheme are supported by numerical examples.